Implementation Plan in Response to The Board : Endorsed Recommendations from the IEO Evaluation on IMF Advice on Capital Flows. (Policy Papers; Policy Paper ;, 2021)
The actions in this document aim at -- Bringing the Fund's framework for advice on capital flow policies up to date with recent research and lessons from experience. -- Enhancing and coordinating a Fund-wide research -- Ramping up the monitoring and analysis of capital flows. -- Strengthening multilateral cooperation on policy issues affecting capital flows.